Diversidade e frugivoria por morcegos em um remanescente de floresta semidecidual de Uberlândia, MG - Pires, Luís Paulo (2012)
In tropical environments, bat species may account for over 50% of the composition of mammals‟ communities. Their importance, however, goes much beyond their contribution to biodiversity. They are also highly diverse in their ecological functions: they are vectors of important medical-veterinary diseases, reduce damage to agriculture, pollinate several plant species and disperse the seeds of many others. Thus, bats are insightful models for the study of theoretical and practical ecology, and the results of these studies may be important for environmental conservation, agriculture and public and veterinary healthcare. Although some bat species are common in urban areas, little is known about the organization of chiropteran communities in these environments and how urbanization and habitat reduction affect community structure and composition. In this sense, the first chapter of this dissertation brings information about the assembly of a bat community from an urban park of Uberlândia, MG, trying to uncover patterns that may be critical for bat conservation in such areas. In respect to the frugivorous bats and plants mutualistic interactions, bats may disperse seeds of more than 500 plant species. In general, the fruits of these plants display traits that, taken together, are known as chiropterocory, or the bat dispersal syndrome. Most studies interpret fruit syndromes as the result of the selective pressure exerted by frugivores. However, the empirical validity of these traits for frugivore selection and of its evolutionary interpretation have been put on debate, since seed dispersal is a generalized process and, therefore, coevolution between frugivores and plants is unlikely. Nevertheless, there‟s a functional relationship between animals body size and the size of the resource which they are able to consume and, therefore, fruit size is an important trait to frugivore selectivity. Thus, if there‟s inter and intraspecific variation in fruit size among plants and frugivores exploit this variation non-randomly, they may exert selective pressure on fruit size. Few are the studies that assess fruit size as an attractive trait to bats and if this trait is subject to selective pressure by these animals. Thereby, the second chapter of this dissertation approaches the interaction between Carollia perspicillata, a frugivorous bat species, and Piper arboreum, which have its fruit consumed as food resource, investigating if bats select preferentially larger fruits and trying to enlighten the role played by bats in the determination of phenotypic plant traits.